Pengaruh pendidikan gizi terhadap pengetahuan, praktik gizi seimbang dan status gizi pada anak sekolah dasar - Irnani, Hayda; Sinaga, Tiurma (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2017)
Background : The prevalence of nutritional problem in school aged children was high, beside Indonesia has Nutritional Balance Guidelines. Socialization of this guidelines in nutrition education and nutrition practice to be applied is very important to do in school aged children.Objective: Analyze nutrition education effect on nutritional knowledge, nutritional practice and nutritional status in Elementary school children.Methods: This study used pra experimental with one group pretest-posttest design. This study was conducted in March – April 2017 in SDN Paringin 2 South Kalimantan. Subjects consisted of 61 students that choosen purposively. The research divided into 4 phases. First phase was pretest, second phase were intervention and first post test of nutritional knowledge, third phase was observation of nutrtitional practice, and the last phase was post test.Result: Nutrition education increased the category of nutritional knowledge from poor to fair. Nutrition education did not increase nutritional practice significantly yet. Nutritional status showed changes in every category and most of the subjects were normal. The difference test showed that nutrition education has a significant difference on pre test and first post test of nutrition knowledge (p=0.000; p<0.05), energy intake  (p=0.002; p<0.05), protein intake (p=0.001; p<0.05), and fat intake (p=0.007; p<0.05). The correlation test showed that there were no significant correlation between sujects’ characteristic with nutritional status and food consumption (p>0.05), nutritional knowledge with nutritional status and nutritional practice(p>0.05), except second post test of nutritional knowledge with fourth nutritional practice observation (p=0.001; p<0.05). Conclusions: There was an increased of nutritional knowledege from poor categorize to fair categorize after the intervention. There were increased and decreased on nutritional practice after intervention. There was no significant different of nutritional status before and after intervention.